Teachers’ Perceptions of the Implementation of Multimodal Pedagogies in Teaching Writing in Indonesian vocational high schools - Armawan, Armawan; Atmowardoyo, Haryanto; Baa, Sultan (Celebes Journal of Language Studies, 2023)
This research aims to describe teachers’ perceptions of implementing multimodal pedagogies in teaching writing. This research is undertaken at SMKS YAPIS Biak, Biak Numfor Regency, Papua Province. This research applies a descriptive qualitative design. The researcher uses the purposive sampling technique to get the sample. The participants in this research are two English teachers. The research instruments are observation, interview, and documentation. For the data analysis technique, the researcher carries out some steps: data condensation, data display, and conclusion drawing and verification. This research result shows that the teachers’ perceptions of the implementation of multimodal pedagogies in teaching writing have similar statements. They have positive perceptions based on their purpose, problems faced, supporting factors in implementing multimodal pedagogies, and their opinions about implementing multimodal pedagogies.